Physical characteristics of youth elite golfers and their relationship with driver clubhead speed - Coughlan, D.; Taylor, M. J.; Jackson, J.; Ward, N.; Beardsley, C. (The Journal of Strength and Conditioning Research, 2020)
Increased clubhead speed (CHS) has a strong relationship with golf performance and is related to athletic qualities in adult golfers. Research investigating the youth golfer is limited. The purpose of this study was to explore the relationships between strength and power on CHS in youth golfers. A correlational design was used to assess relationships between CHS and anthropometric, strength, and power measurements. Thirty-six male and 33 female golfers aged 13-17 took part in this study. Male golfers showed significant relationships between CHS and handicap (HCP) (r = -0.50), seated medicine ball throw to the left (SMBTL) (r = 0.67), and right (SMBTR) (r = 0.61), rotational medicine ball throw to the left (RMBTL) (r = 0.71), and right RMBTR (r = 0.62). Female golfers showed significant relationships between CHS and HCP (r = -0.52), mass (r = 0.72), countermovement jump power (r = 0.60), RMBTL (r = 0.57), RMBTR (r = 0.56). Multiple stepwise linear regression analysis identified 77% of the variance in CHS could be explained through SMBTL and RMBTL in males. In females, 84% of the variance in CHS could be explained through mass, RMBTR, and height. This study demonstrated relationships between CHS and body mass and upper-, lower-, and full-body concentric dominant power exercises. This study could aid in the development of training interventions for youth golfers.